Establishment of genetic transformation system and initial report of transform BIO and bio gene in Petunia hybrida - LI Ying; LIU Jiyan; HU Jiangqin; CHEN Zhehao; HU Lingzhi; WANG Lilin (浙江大学学报. 农业与生命科学版, 2013)
BIO ORGANS (BIO) gene is located on the short arm of Chromosome Ⅳ in Lotus japonicus. The bio mutant is obtained from a large scale EMS mutagenesis screen. Gene sequencing have proved that a stop coden appeared earlier in the transcripts of BIO by a retrotransposon insertion, which led to a truncated protein. Morphological analysis showed that the bio mutant displayed enlarged plant organs and a better symmetry in flower. It has been speculated that LjBIO regulate organ morphology and plant size in Lotus japonicus. However, the function and regulation mechanism of LjBIO still remains unclear.Petunia hybrida is a good material for genetic engineering and molecular biology research, due to its short life-cycle, simple growing conditions and mature transgenic system mediated by agrobacterium infiltration. Calli tissues are induced from P. hybrida QL01 explants as transgenic materials in order to gain further information about the function and possible mechanism of LjBIO.The tissue culture and regeneration system of P. hybrid was refined. Different explants from P. hybrida QL01 were chosen and several concentration gradients of 6-BA and NAA were tested for selecting the best tissue culture and regeneration system. Agrobacterium mediated gene transformation was used to induce BIO and the mutant gene bio into the calli of QL01. The 35S-BIO-GFP and 35S-bio-GFP vectors were transferred into agrobacterium GV3101 by freezing and defreezing immediately using nitrogen and water bath. The target agrobacteria clones were verified by PCR and were cultured overnight into large volume. The agrobacterium were resuspended in MS liquid medium, used to infiltrate the pre-cultured explants for 8 minutes and co-cultured for another 3 days in dark. Transgenic plants were obtained and confirmed with hygromycin screening and RT-PCR detection. The phenotypes of transgenic plants were recorded and analyzed to obtain more information about the gene function.Results showed that MS medium with 0.1 mg/L 6-BA was suitable for the growth of P. hybrid and the proliferation of calli from the excised stem. MS medium with 1.0 mg/L 6-BA and 0.1 mg/L NAA was best for the bud regeneration. 0.3 mg/L hygromycin was used for resistance screening and 20 different resistant plants were obtained for both BIO and its mutant gene bio respectively. PCR detection of gene expression showed that 15 35S-BIO and 17 35S-bio transgenic plants had been successfully obtained. Morphological analysis displayed that both 35S-BIO and 35S-bio transgenic plants had abnormal leaves with irregular margins, some of them even showed a tendency that one leaf would be divided into two. In 35S-BIO transgenic plants, certain blades had smaller size and became thinner than the wild-type and a few of them only had main veins left. Detailed data showed that leaf surface area and length-width ratio altered obviously.The ectopic and over-expression of LjBIO and Ljbio in P. hybrida revealed that this gene affected not only the size of plant and the symmetry of floral organs, but also influenced the development and morphology of leaf. The study illustrated the essential role of LjBIO gene in maintaining leaf morphology, and displayed that the 3′ end of LjBIO had its unique function worthy of further research according to the different leaf phenotypes between 35S-BIO and 35S-bio transgenic plants. This work also provided experimental basis for the further study of regulatory mechanism of LjBIO gene.